1986
DOI: 10.1115/1.3171805
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Dynamic Tensile Test

Abstract: A numerical investigation of the tensile test using a finite-difference, one-dimensional elasto-viscoplastic code is presented. The influence of strain rate, strain rate sensitivity, and inertia on the development of the axial particle velocity, stress, strain, and strain rate profiles in pure copper is studied. The initial stages of post-uniform deformation and the stabilizing influence of inertia and strain rate sensitivity in this regime are demonstrated. Both inertia and strain rate sensitivity are shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…There have been a number of attempts to capture the effect of inertia on neck development using simplified one-dimensional models (Regazzoni et al, 1986;Tuggu et al, 1990). Here, a two-state model is …”
Section: Two-state Model For Dynamic Neck Developmentmentioning
confidence: 99%
“…There have been a number of attempts to capture the effect of inertia on neck development using simplified one-dimensional models (Regazzoni et al, 1986;Tuggu et al, 1990). Here, a two-state model is …”
Section: Two-state Model For Dynamic Neck Developmentmentioning
confidence: 99%
“…Relying on the seminal work of Regazzoni et al (1986), we develop a simple finite difference model to describe the mechanical response of steel bars subjected to dynamic tension. Our explicit numerical approach lies within the spirit of the scheme recently developed by Kudryashov et al (2015) to investigate the onset and development of shear bands in metallic solids subjected to dynamic loading.…”
Section: Finite Difference Modelmentioning
confidence: 99%
“…The numerical studies on the dynamic necking problem started in the late 1980s and early 1990s with the pioneering works of Regazzoni et al (1986), Needleman and co-workers (Tvergaard and Needleman, 1990;Needleman, 1991;Knoche and Needleman, 1993) and Nemes and Eftis (1993). One advantage of the numerical calculations is that, unlike the linear stability analyses, they allow us to investigate the spatio-temporal development of the instability.…”
Section: Introductionmentioning
confidence: 98%
“…They found that inertia has a strong stabilizing effect on the void growth process, and effects of strain hardening and thermal softening are relatively small. Through their theoretical study of dynamic tensile tests, Regazzoni and co-workers 37 showed that in all cases, inertia enhances ductility of materials. The works of many investigators 14,38,39 showed the same results.…”
Section: B Previous Workmentioning
confidence: 99%
“…This result was also given by Regazzoni and co-workers's work. 37 They numerically investigated dynamic tensile tests (⑀ Ͼ10 3 s Ϫ1 ) using a finite-difference method and found that at a strain rate exceeding 10 3 s Ϫ1 , inertia and strain-rate sensitivity lead to the effect of the same order of magnitude. The above information indicates that in the case of strain rates being in the range of 10 3 -10 7 s Ϫ1 , the rates of deformation (Ė d ) and kinetic (Ė k ) energies have the same order of magnitude.…”
Section: ͑75͒mentioning
confidence: 99%